The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1469-8749.2007.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health in young adults with spina bifida

Abstract: The aims of this study were to compare the perceived health of young adults with spina bifida with a population without disability, and to determine the effect of the disease characteristics and resulting impairments on perceived health. This cross-sectional study is part of the Adolescents with Spina Bifida in the Netherlands study. Data were collected by physical examination and a questionnaire. In total, 179 patients (age range 16-25y) participated in the study and perceived health data were completed for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 25 publications
8
36
0
5
Order By: Relevance
“…25 Furthermore, compared with their male counterparts, females with myelomeningocele have reported lower rates of employment 26,27 and decreased QOL. 28 However, until now, no study has examined sex differences in transition outcomes across multiple domains of health management and psychosocial functioning. Research on transition outcomes among young adults with myelomeningocele in the USA is particularly restricted in scope.…”
mentioning
confidence: 99%
“…25 Furthermore, compared with their male counterparts, females with myelomeningocele have reported lower rates of employment 26,27 and decreased QOL. 28 However, until now, no study has examined sex differences in transition outcomes across multiple domains of health management and psychosocial functioning. Research on transition outcomes among young adults with myelomeningocele in the USA is particularly restricted in scope.…”
mentioning
confidence: 99%
“…No significant or meaningful differences were found for mental health and role-emotional scales [69].…”
Section: Quantitative Perspectivementioning
confidence: 71%
“…There were 15 studies that used qualitative methods [9,12,[75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Their findings indicated that SB affected the following aspects of patients' lives: self-image [9], feelings and emotions [75,77], social life [9,22,69,78], acceptance [9], independence [9], impact on school [75,77,85] impact on parents and siblings [9,76,[78][79][80] and concerns about the future [12,80,82,87]. In addition, patients' ability to cope with and adapt to SB has also been well documented.…”
Section: Qualitative Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the context in which patients live and the availability of family support are very important in determining quality of life and the degree of psycho-physical well-being achieved by patients (13)(14)(15). Verhoef et al have published several articles on the quality of life, satisfaction, independence and sexuality in Spina Bifida patients (16)(17)(18). Their latest paper of 2007 compared the self-reported health condition of young adults with Spina Bifida with that of healthy peers.…”
Section: Introductionmentioning
confidence: 99%